Proteomics Insights Into the Molecular Basis of SARS-CoV-2 Infection: What We Can Learn From the Human Olfactory Axis - Lachén-Montes, Mercedes; Corrales, Fernando J.; Fernández-Irigoyen, Joaquín; Santamaría, Enrique (Frontiers in Microbiology, 2020)
Like other RNA viruses, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) replicates in host cells continuously modulating the molecular environment. It encodes 28 multifunctional proteins that induce an imbalance in the metabolic and proteostatic homeostasis in infected cells. Recently, proteomic approaches have allowed the evaluation of the impact of SARS-CoV-2 infection in human cells. Here, we discuss the current use of proteomics in three major application areas: i) viral-protein interactomics, (ii) differential proteotyping to map the virally induced changes in different cell types and (iii) diagnostic methods for Coronavirus infectious disease 2019 (COVID-19). Since the nasal cavity is the entry site for SARS-CoV-2, we will also discuss the potential application of olfactory proteomics to provide novel insights about the olfactory dysfunction triggered by SARS-CoV-2 in COVID-19 patients.